Anode and zinc secondary battery
Patent Information
- Application Number
- JP2022566801
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-03
- Filing Date
- 2021-11-08
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-11-08
Smart Images

Figure 0007641989000004 
Figure 0007641989000005 
Figure 0007641989000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode and a zinc secondary battery. [Background technology]
[0002] In zinc secondary batteries such as nickel-zinc secondary batteries and air-zinc secondary batteries, it is known that metallic zinc precipitates in the form of dendrites from the negative electrode during charging, penetrates the voids in the separator such as nonwoven fabric, and reaches the positive electrode, resulting in a short circuit. Such a short circuit caused by zinc dendrites shortens the repeated charge-discharge life.
[0003] In order to address the above problems, a battery has been proposed that includes a layered double hydroxide (LDH) separator that selectively allows hydroxide ions to pass through while preventing the penetration of zinc dendrites. For example, Patent Document 1 (WO 2013 / 118561) discloses that an LDH separator is provided between the positive and negative electrodes in a nickel-zinc secondary battery. In addition, Patent Document 2 (WO 2016 / 076047) discloses a separator structure that includes an LDH separator fitted or joined to a resin outer frame, and that the LDH separator has such high density that it is gas impermeable and / or water impermeable. This document also discloses that the LDH separator can be composited with a porous substrate. Furthermore, Patent Document 3 (WO 2016 / 067884) discloses various methods for obtaining a composite material by forming an LDH dense membrane on the surface of a porous substrate. This method includes the steps of uniformly attaching an initiator substance capable of providing an initiation point for the crystal growth of LDH to a porous substrate, and subjecting the porous substrate to hydrothermal treatment in a raw material aqueous solution to form a dense LDH membrane on the surface of the porous substrate.
[0004] Meanwhile, another factor that shortens the life of zinc secondary batteries is the change in the morphology of zinc, which is the negative electrode active material. That is, as zinc dissolves and precipitates repeatedly due to repeated charging and discharging, the morphology of the negative electrode changes, causing high resistance due to blockage of pores, a decrease in the charge active material due to accumulation of isolated zinc, etc., resulting in a problem that charging and discharging becomes difficult. In order to address this problem, Patent Document 4 (WO 2020 / 049902) proposes using ZnO particles in combination with at least two selected from (i) metal Zn particles of a predetermined particle size, (ii) a predetermined metal element, and (iii) a binder resin having a hydroxyl group for use in the negative electrode. It is said that this negative electrode can suppress the deterioration of the negative electrode due to repeated charging and discharging in a zinc secondary battery, improve durability, and thereby extend the cycle life.
[0005] Furthermore, Patent Document 5 (Japanese Patent No. 6,190101) discloses a negative electrode composite material that contains a negative electrode active material such as metallic Zn or ZnO; a polymer such as an aromatic group-containing polymer, an ether group-containing polymer, or a hydroxyl group-containing polymer; and a conductive assistant that is a compound of elements such as B, Ba, Bi, Br, Ca, Cd, Ce, Cl, F, Ga, Hg, In, La, or Mn. It is described that the negative electrode composite material is suitable for forming a storage battery that exhibits excellent battery performance such as high cycle characteristics, rate characteristics, and Coulombic efficiency while suppressing shape changes in the electrode active material, morphological changes in the electrode active material such as dendrites, dissolution, corrosion, and passivation. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2013 / 118561 [Patent Document 2] International Publication No. 2016 / 076047 [Patent Document 3] International Publication No. 2016 / 067884 [Patent Document 4] International Publication No. 2020 / 049902 [Patent Document 5] Patent No. 6190101 Summary of the Invention
[0007] As disclosed in Patent Documents 4 and 5, various attempts have been proposed to address the deterioration of cycle characteristics associated with morphological changes in the zinc negative electrode, but further improvement in cycle characteristics is required.
[0008] The present inventors have now discovered that by using a composite material containing Zn particles, ZnO particles, and a predetermined amount of nonionic water-absorbing polymer in the negative electrode, deterioration of the negative electrode caused by repeated charging and discharging in a zinc secondary battery can be suppressed, durability can be improved, and the cycle life can be extended.
[0009] Therefore, an object of the present invention is to provide a negative electrode which can suppress deterioration of the negative electrode caused by repeated charging and discharging, improve durability, and thereby extend cycle life.
[0010] According to one aspect of the present invention, there is provided a negative electrode for use in a zinc secondary battery, comprising: A negative electrode active material including ZnO particles and Zn particles; A nonionic water-absorbing polymer; When the content of the ZnO particles is taken as 100 parts by weight, the nonionic water-absorbing polymer is contained in an amount of 0.01 to 6.0 parts by weight in terms of solid content.
[0011] According to another aspect of the present invention, A positive electrode and The negative electrode; a separator that separates the positive electrode and the negative electrode in a manner capable of conducting hydroxide ions; An electrolyte; A zinc secondary battery is provided, comprising: [Brief description of the drawings]
[0012] [Figure 1A] FIG. 2 is a conceptual diagram for explaining a presumed mechanism of a phenomenon occurring during a charging reaction of a negative electrode according to the present invention. [Figure 1B] FIG. 2 is a conceptual diagram for explaining a presumed mechanism of a phenomenon occurring during a discharge reaction of a negative electrode according to the present invention. [Diagram 2] 1 is a graph showing an example of the relationship between the amount of water absorbed and the amount of KOH collected per 1 cm 3 of nonionic water-absorbing polymer, and the KOH concentration. [Diagram 3] 1 is an image obtained by observing, by SEM, a cross section of a negative electrode in an end-of-discharge state immediately after 40 charge-discharge cycles in an evaluation cell of Example 5 containing a nonionic water-absorbing polymer. [Figure 4] 1 is an image obtained by observing, by SEM, a cross section of a negative electrode in a state at the end of discharge immediately after 40 charge-discharge cycles in an evaluation cell of Example 1 (comparative example) not containing a nonionic water-absorbing polymer. [Diagram 5] 1 is an image obtained by observing, by SEM, a cross section of a negative electrode in an end-of-discharge state in which the capacity retention rate had deteriorated to 50% through repeated charge-discharge cycles in an evaluation cell of Example 5 containing a nonionic water-absorbing polymer. [Figure 6] 1 is an image obtained by observing, by SEM, a cross section of a negative electrode at the end of discharge in an evaluation cell of Example 1 (comparative example) not containing a nonionic water-absorbing polymer, where the capacity retention rate had deteriorated to 45% through repeated charge-discharge cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The negative electrode of the present invention is a negative electrode used in a zinc secondary battery. This negative electrode includes a negative electrode active material and a nonionic water-absorbing polymer. The negative electrode active material includes ZnO particles and Zn particles. In particular, this negative electrode includes 0.01 to 6.0 parts by weight of a nonionic water-absorbing polymer in terms of solid content when the content of ZnO particles is 100 parts by weight. By using a composite material including a predetermined amount of a nonionic water-absorbing polymer together with Zn particles and ZnO particles in the negative electrode, deterioration of the negative electrode due to repeated charging and discharging in the zinc secondary battery can be suppressed, durability can be improved, and cycle life can be extended.
[0014] As mentioned above, in the conventional negative electrode, as zinc dissolves and precipitates repeatedly due to repeated charging and discharging, the negative electrode changes in shape, causing high resistance due to pore blockage and a decrease in the charge active material due to the accumulation of isolated zinc, which results in problems such as difficulty in charging and discharging. Such problems can be effectively suppressed or solved by adding a nonionic water-absorbing polymer to the negative electrode. Although the mechanism is unclear, it is believed to be due to the fact that the nonionic water-absorbing polymer has a property that the liquid absorption property changes according to the change in pH. For example, it is speculated that the following phenomenon occurs because the nonionic water-absorbing polymer has a property that the water absorption ability decreases with an increase in pH and releases water. The microscopic structure of the negative electrode 10 is conceptually shown in Figures 1A and 1B. In these figures, the negative electrode 10 includes a negative electrode active material 12 provided on a current collector 16 and a nonionic water-absorbing polymer 14 covering it, and is depicted in a state immersed in an electrolyte 18. First, during the charging reaction, as shown in FIG. 1A, ZnO+H2O+2e - →Zn+2OH - The reaction at the negative electrode 10 proceeds based on - As the pH of the electrolyte increases, that is, as the pH rises, the nonionic water-absorbing polymer 14 loses its liquid-absorbing ability and releases the water it has retained to the negative electrode active material 12, thereby assisting the charging reaction. In other words, the nonionic water-absorbing polymer 14 conveniently supplies water to the charging reaction, which consumes water, thereby allowing the charging reaction to continue. On the other hand, in the discharge reaction, as shown in FIG. 1B, Zn+2OH - →ZnO+H2O+2e - The reaction proceeds based on OH -With the decrease in pH, that is, the decrease in pH, the nonionic water-absorbing polymer 14 increases its liquid absorption ability, and absorbs the water generated in the negative electrode active material 12, thereby assisting the above-mentioned discharge reaction. In other words, the nonionic water-absorbing polymer 14 conveniently absorbs water for the discharge reaction in which water is generated, thereby continuing the discharge reaction. In this way, the nonionic water-absorbing polymer 14 absorbs or releases water due to the pH fluctuation during the charge and discharge reaction, and the reaction inside the negative electrode 10 continues and becomes uniform, and as a result, the deterioration of the negative electrode 10 due to repeated charge and discharge is suppressed, and durability is improved, and it is considered that the cycle life is thereby extended. In this regard, if the reaction inside the negative electrode 10 cannot be continued, the battery reaction will proceed intensively only at the part where the electrolyte 18 is abundant (for example, only in the vicinity of the nonwoven fabric in the case where it is provided), and the negative electrode active material 12 will be used unevenly, which is considered to be a factor in the decrease in capacity. The advantageous effect of the present invention described above is a unique effect due to the selection of the nonionic water-absorbing polymer 14. In fact, when an ionic absorbent polymer (such as polyacrylic acid or potassium polyacrylate) is added, the above-mentioned effect is not obtained, and the cycle characteristics are rather deteriorated.
[0015] The negative electrode active material 12 includes Zn particles and ZnO particles. The Zn particles are typically metal Zn particles, but particles of a Zn alloy or a Zn compound may be used. Metal Zn particles generally used in zinc secondary batteries can be used as the metal Zn particles, but it is more preferable to use metal Zn particles smaller than the metal Zn particles in terms of extending the cycle life of the battery. Specifically, the average particle size D50 of the metal Zn particles is preferably 5 to 200 μm, more preferably 50 to 200 μm, and even more preferably 70 to 160 μm. The preferred content of the Zn particles in the negative electrode 10 is preferably 1.0 to 87.5 parts by weight, more preferably 3.0 to 70.0 parts by weight, and even more preferably 5.0 to 55.0 parts by weight, when the content of the ZnO particles is 100 parts by weight. The metal Zn particles may be doped with a dopant such as In or Bi. The ZnO particles are not particularly limited and may be a commercially available zinc oxide powder used in zinc secondary batteries or a zinc oxide powder obtained by growing particles by a solid-phase reaction using the commercially available zinc oxide powder as a starting material. The average particle size D50 of the ZnO particles is preferably 0.1 to 20 μm, more preferably 0.1 to 10 μm, and further preferably 0.1 to 5 μm. In this specification, the average particle size D50 means a particle size at which the cumulative volume from the small particle size side in the particle size distribution obtained by a laser diffraction / scattering method is 50%.
[0016] The negative electrode 10 preferably further contains one or more metal elements selected from In and Bi. These metal elements can suppress the generation of undesirable hydrogen gas due to self-discharge of the negative electrode 10. These metal elements may be contained in the negative electrode 10 in any form such as metal, oxide, hydroxide, other compound, etc., but are preferably contained in the form of oxide or hydroxide, and more preferably in the form of oxide particles. Examples of the oxides of the above metal elements include In2O3, Bi2O3, etc. Examples of the hydroxides of the above metal elements include In(OH)3, Bi(OH)3, etc. In any case, when the content of the ZnO particles is 100 parts by weight, the content of In is preferably 0 to 2 parts by weight in terms of oxide, and the content of Bi is preferably 0 to 6 parts by weight in terms of oxide, and more preferably the content of In is 0 to 1.5 parts by weight in terms of oxide, and the content of Bi is preferably 0 to 4.5 parts by weight in terms of oxide. When In and / or Bi are contained in the negative electrode 10 in the form of oxide or hydroxide, it is not necessary that all of In and / or Bi are in the form of oxide or hydroxide, and a part of them may be contained in the negative electrode in other forms such as metal or other compounds. For example, the above metal elements may be doped into metal Zn particles as trace elements. In this case, the In concentration in the metal Zn particles is preferably 50 to 2000 ppm by weight, more preferably 200 to 1500 ppm by weight, and the Bi concentration in the metal Zn particles is preferably 50 to 2000 ppm by weight, more preferably 100 to 1300 ppm by weight.
[0017] The nonionic water-absorbing polymer 14 can be any commercially available nonionic water-absorbing polymer, but as described above, it is preferable that the polymer has a property that the liquid absorption property changes according to the change in pH. 32 shows an example of the relationship between the amount of water absorbed and the amount of KOH collected per unit time and the KOH concentration. As shown in FIG. 2, the amount of water absorbed changes with the change in the KOH concentration in the electrolyte (i.e., the change in pH), but a material that does not change the amount of KOH collected significantly is preferred in that it can absorb or release only water with pH fluctuation. In particular, a material that exhibits a behavior in which the amount of water absorbed decreases with an increase in pH is preferred. Preferred examples of such nonionic water-absorbing polymer 14 include polyalkylene oxide-based water-absorbing resins, polyvinyl acetamide-based water-absorbing resins, polyvinyl alcohol (PVA resin), and polyvinyl butyral (PVB resin), and more preferably polyalkylene oxide-based water-absorbing resins. As the polyalkylene oxide-based water-absorbing resin, commercially available products can be used. The nonionic water-absorbing polymer may contain at least one selected from hydrophilic ether groups, hydroxyl groups, amide groups, and acetamide groups. The presence of these functional groups makes it possible to obtain a water-absorbing and releasing function that is more favorable for the battery reaction. The nonionic water-absorbing polymer may be present as particles in the negative electrode, or may cover the active material. When the active material is covered with the nonionic water-absorbing polymer, a method of adding the nonionic water-absorbing polymer in a slurry state, or a method of heating and melting the nonionic water-absorbing polymer during production can be considered. In the latter case, the melting point of the nonionic water-absorbing polymer is preferably 45°C to 350°C, more preferably 45°C to 200°C, and even more preferably 50°C to 100°C.
[0018] The content of the nonionic water-absorbing polymer 14 in the negative electrode 10 is preferably 0.01 to 6.0 parts by weight, more preferably 0.01 to 5.5 parts by weight, even more preferably 0.05 to 5.0 parts by weight, and particularly preferably 0.07 to 4.0 parts by weight, in terms of solid content, when the content of the ZnO particles is taken as 100 parts by weight. The nonionic water-absorbing polymer 14 is preferably particulate. In this case, the particle size of the nonionic water-absorbing polymer 14 is preferably 10 to 200 μm, more preferably 15 to 180 μm, even more preferably 20 to 160 μm, and particularly preferably 30 to 150 μm. It is not necessary that all the particles of the nonionic water-absorbing polymer 14 are within the above numerical range, and it is sufficient that the average particle size D50 falls within the above numerical range.
[0019] The negative electrode 10 may further include a conductive additive. Examples of the conductive additive include carbon, metal powder (such as tin, lead, copper, and cobalt), and precious metal paste.
[0020] The negative electrode 10 may further contain a binder resin (not shown). When the negative electrode 10 contains a binder, the shape of the negative electrode is easily maintained. As the binder resin, various known binders can be used, and preferred examples include polyvinyl alcohol (PVA) and polytetrafluoroethylene (PTFE). It is particularly preferred to use a combination of both PVA and PTFE as the binder.
[0021] The negative electrode 10 is preferably a sheet-like pressed body. This can prevent the negative electrode active material 12 from falling off, improve the electrode density, and more effectively suppress the change in shape of the negative electrode 10. Such a sheet-like pressed body can be produced by adding a binder to the negative electrode material and kneading the mixture, and then subjecting the resulting kneaded mixture to press molding such as roll pressing to form it into a sheet.
[0022] The negative electrode 10 is preferably provided with a current collector 16. Preferable examples of the current collector 16 include copper punched metal and copper expanded metal. In this case, for example, a mixture containing Zn particles, ZnO particles, solder, and optionally a binder resin (e.g., polytetrafluoroethylene particles) can be applied onto the copper punched metal or copper expanded metal to preferably prepare a negative electrode plate consisting of the negative electrode 10 / current collector 16. In this case, it is also preferable to perform a press treatment on the negative electrode plate (i.e., the negative electrode 10 / current collector 16) after drying to prevent the negative electrode active material 12 from falling off and to improve the electrode density. Alternatively, the above-mentioned sheet-like press molded body may be pressure-bonded to the current collector 16 such as copper expanded metal.
[0023] Zinc secondary battery The negative electrode 10 of the present invention is preferably applied to a zinc secondary battery. Therefore, according to a preferred embodiment of the present invention, a zinc secondary battery is provided, which includes a positive electrode (not shown), a negative electrode 10, a separator that separates the positive electrode and the negative electrode 10 so as to be capable of conducting hydroxide ions, and an electrolyte 18. The zinc secondary battery of the present invention is not particularly limited as long as it is a secondary battery that uses the above-mentioned negative electrode 10 and the electrolyte 18 (typically an aqueous alkali metal hydroxide solution). Therefore, it can be a nickel-zinc secondary battery, a silver oxide zinc secondary battery, a manganese oxide zinc secondary battery, a zinc-air secondary battery, or any other type of alkaline zinc secondary battery. For example, it is preferable that the positive electrode contains nickel hydroxide and / or nickel oxyhydroxide, thereby forming a nickel-zinc secondary battery. Alternatively, the positive electrode may be an air electrode, thereby forming a zinc secondary battery.
[0024] The separator is preferably a layered double hydroxide (LDH) separator. That is, as described above, in the field of nickel-zinc secondary batteries and air-zinc secondary batteries, LDH separators are known (see Patent Documents 1 to 3), and this LDH separator can be preferably used in the zinc secondary battery of the present invention. The LDH separator can selectively allow hydroxide ions to pass through while preventing the penetration of zinc dendrites. In combination with the effect of the negative electrode of the present invention, the durability of the zinc secondary battery can be further improved. In this specification, the LDH separator is defined as a separator containing a layered double hydroxide (LDH) and / or an LDH-like compound (hereinafter collectively referred to as a hydroxide ion conductive layered compound), which selectively passes hydroxide ions by utilizing the hydroxide ion conductivity of the hydroxide ion conductive layered compound. In this specification, the "LDH-like compound" is a hydroxide and / or oxide having a layered crystal structure similar to LDH, which may not be called LDH, and can be said to be equivalent to LDH. However, in a broad sense, "LDH" can be interpreted as including not only LDH but also LDH-like compounds.
[0025] The LDH separator may be a composite with a porous substrate as disclosed in Patent Documents 1 to 3. The porous substrate may be made of any of ceramic materials, metal materials, and polymer materials, but is particularly preferably made of a polymer material. The polymer porous substrate has the following advantages: 1) flexibility (so it is difficult to break even if it is made thin); 2) it is easy to increase the porosity; 3) it is easy to increase the conductivity (because the thickness can be reduced while increasing the porosity); and 4) it is easy to manufacture and handle. Particularly preferred polymer materials are polyolefins such as polypropylene and polyethylene, which are excellent in hot water resistance, acid resistance, and alkali resistance, and are low cost, and most preferably polypropylene. When the porous substrate is made of a polymer material, it is particularly preferred that the hydroxide ion conductive layered compound is incorporated throughout the entire thickness of the porous substrate (for example, most or almost all of the pores inside the porous substrate are filled with the hydroxide ion conductive layered compound). In this case, the preferred thickness of the polymer porous substrate is 5 to 200 μm, more preferably 5 to 100 μm, and even more preferably 5 to 30 μm. As such a polymeric porous substrate, a microporous membrane such as that commercially available as a lithium battery separator can be preferably used.
[0026] The electrolyte 18 preferably contains an aqueous solution of an alkali metal hydroxide. Examples of the alkali metal hydroxide include potassium hydroxide, sodium hydroxide, lithium hydroxide, and ammonium hydroxide, with potassium hydroxide being more preferred. Zinc oxide, zinc hydroxide, and the like may be added to the electrolyte to suppress self-dissolution of the zinc-containing material. EXAMPLES
[0027] The present invention will now be further illustrated by the following examples.
[0028] Examples 1 to 50 (1) Preparation of the positive electrode Paste-type nickel hydroxide positive electrode (capacity density: approx. 700 mAh / cm 3 ) was prepared.
[0029] (2) Preparation of the negative electrode The following various raw material powders were prepared. ZnO powder (Seido Chemical Industry Co., Ltd., JIS standard class 1 grade, average particle size D50: 0.2 μm) Metallic Zn powder (manufactured by DOWA Electronics Co., Ltd., doped with Bi and In, Bi: 70 ppm by weight, In: 200 ppm by weight, average particle size D50: 120 μm) In2O3 powder (manufactured by High Purity Chemical Laboratory Co., Ltd., purity: 99.99%), average particle size D50: adjusted to 1.0 μm Bi2O3 powder (manufactured by High Purity Chemical Laboratory Co., Ltd., purity: 99.99%, average particle size D50: adjusted to 1.0 μm) Nonionic water-absorbing polymer (polyalkylene oxide-based water-absorbing resin, manufactured by Sumitomo Seika Chemicals Co., Ltd., Aquacaulk, grade: TWB-P, product form: powder, average particle size D50: 50μm or 130μm) - Ionic water-absorbing polymer (polyacrylic acid, manufactured by Sumitomo Seika Chemicals Co., Ltd., AQUPEC HV) · Ionic water-absorbing polymer (potassium polyacrylate, Sigma-Aldrich, Poly partial potassium salt)
[0030] According to the blending ratios shown in Tables 1 and 2, ZnO powder was mixed with metal Zn powder, polytetrafluoroethylene (PTFE), and optionally In2O3 powder, Bi2O3 powder, and / or nonionic water-absorbing polymer, and kneaded with propylene glycol. In Examples 17 to 19, 21 to 23, 27 to 29, and 41 to 43, the nonionic water-absorbing polymer was dispersed in water and added in the form of a slurry. The resulting kneaded product was rolled with a roll press to obtain a negative electrode active material sheet. The negative electrode active material sheet was pressure-bonded to a tin-plated copper expand metal to obtain a negative electrode.
[0031] (3) Preparation of electrolyte Ion-exchanged water was added to a 48% aqueous potassium hydroxide solution (special grade, manufactured by Kanto Chemical Co., Ltd.) to adjust the KOH concentration to 5.4 mol%, and then 0.42 mol / L of zinc oxide was dissolved therein by heating and stirring to obtain an electrolyte.
[0032] (4) Preparation of evaluation cell The positive and negative electrodes were wrapped in nonwoven fabric, and a current extraction terminal was welded to them. The positive and negative electrodes thus prepared were placed opposite each other via an LDH separator, sandwiched between a laminate film with a current extraction port, and three sides of the laminate film were heat-sealed. An electrolyte was added to the cell container with the top open in this way, and the electrolyte was allowed to fully penetrate the positive and negative electrodes by evacuation or the like. The remaining side of the laminate film was then heat-sealed to form a simple sealed cell.
[0033] (5) Evaluation <Cycle characteristics> Using a charge / discharge device (Toyo Systems Co., Ltd., TOSCAT3100), the simple sealed cell was subjected to formation with 0.1C charge and 0.2C discharge. Then, a 1C charge / discharge cycle was performed. The charge / discharge cycle was repeated under the same conditions, and the number of charge / discharge cycles until the discharge capacity of the prototype battery decreased to 70% of the discharge capacity of the first cycle was recorded, and this was used as an index of cycle characteristics. The results are shown in Tables 1 to 3, and it was confirmed that the addition of nonionic water-absorbing polymers improved the cycle characteristics for negative electrodes of various compositions. In addition, it was confirmed from the results shown in Table 3 that the cycle characteristics rather decreased when ionic absorbent polymers were added.
[0034] <Observation of microstructure after 40 cycles> In the evaluation cell of Example 5 containing the nonionic water-absorbing polymer, the cross section of the negative electrode in the end of discharge state immediately after 40 charge-discharge cycles was observed by SEM, and the image shown in FIG. 3 was obtained. Similarly, in the evaluation cell of Example 1 (Comparative Example) not containing the nonionic water-absorbing polymer, the cross section of the negative electrode in the end of discharge state immediately after 40 charge-discharge cycles was observed by SEM, and the image shown in FIG. 4 was obtained. In the negative electrode of FIG. 4 to which the nonionic water-absorbing polymer additive was not added, many isolated areas were observed in which the metal Zn was unevenly distributed inside the negative electrode. In contrast, in the negative electrode of FIG. 3 to which the nonionic water-absorbing polymer additive was added, the uneven distribution of the metal Zn inside the negative electrode was significantly suppressed, and it was observed that the reaction inside the negative electrode was uniform, which is considered to have contributed to the improvement of the cycle characteristics.
[0035] <Observation of microstructure after deterioration> In the evaluation cell of Example 5 containing the nonionic water-absorbing polymer, the above charge-discharge cycle was repeated and the cross section of the negative electrode in the end of discharge state deteriorated to a capacity maintenance rate of 50% was observed by SEM, and the image shown in FIG. 5 was obtained. Similarly, in the evaluation cell of Example 1 (Comparative Example) not containing the nonionic water-absorbing polymer, the above charge-discharge cycle was repeated and the cross section of the negative electrode in the end of discharge state deteriorated to a capacity maintenance rate of 45% was observed by SEM, and the image shown in FIG. 6 was obtained. In the negative electrode of FIG. 6 to which the nonionic water-absorbing polymer additive was not added, the metal Zn shown in white in the figure was unevenly accumulated, and the morphological change (macro shape change) of the negative electrode was significantly observed. In contrast, in the negative electrode of FIG. 5 to which the nonionic water-absorbing polymer additive was added, the metal Zn shown in white in the figure was uniformly accumulated, and it was presumed that the morphological change (macro shape change) of the negative electrode was significantly suppressed, and the reaction proceeded uniformly overall.
[0036] [Table 1]
[0037] [Table 2]
[0038]
Table 3
Claims
1. A negative electrode for use in a zinc secondary battery, a negative electrode active material including ZnO particles and Zn particles; A nonionic water-absorbing polymer; One or more metal elements selected from In and Bi; Polytetrafluoroethylene as a binder resin; and the nonionic water-absorbing polymer is contained in an amount of 0.07 to 5.0 parts by weight in terms of solid content when the content of the ZnO particles is taken as 100 parts by weight.
2. A negative electrode for use in a zinc secondary battery, a negative electrode active material including ZnO particles and Zn particles; A nonionic water-absorbing polymer; Including, The negative electrode does not contain In and Bi, and contains 0.05 to 1 part by weight of the nonionic water-absorbing polymer in terms of solid content when the content of the ZnO particles is taken as 100 parts by weight.
3. A negative electrode for use in a zinc secondary battery, a negative electrode active material including ZnO particles and Zn particles; A nonionic water-absorbing polymer; Including, The negative electrode does not contain In and Bi, the nonionic water-absorbing polymer is in the form of particles having a particle diameter of 10 to 50 μm, and the nonionic water-absorbing polymer is contained in an amount of 0.01 to 6.0 parts by weight in terms of solid content when the content of the ZnO particles is taken as 100 parts by weight.
4. The nonionic water-absorbing polymer is at least one selected from the group consisting of polyalkylene oxide-based water-absorbing resin, polyvinyl acetamide-based water-absorbing resin, polyvinyl alcohol (PVA resin), and polyvinyl butyral (PVB resin), the negative electrode according to any one of claims 1 to 3.
5. The negative electrode according to any one of claims 1 to 4, wherein the nonionic water-absorbing polymer is a polyalkylene oxide-based water-absorbing resin.
6. 3. The negative electrode according to claim 1, wherein the nonionic water-absorbing polymer is in the form of particles having a particle size of 10 to 200 μm.
7. The negative electrode according to any one of claims 1 to 6, wherein the nonionic water-absorbing polymer has a property that the liquid absorption property changes according to a change in pH.
8. The negative electrode according to any one of claims 1 to 7, wherein the Zn particles are contained in an amount of 1.0 to 87.5 parts by weight per 100 parts by weight of the ZnO particles.
9. 2. The negative electrode according to claim 1, wherein the content of In is 0 to 2 parts by weight in terms of oxide, and the content of Bi is 0 to 6 parts by weight in terms of oxide, when the content of the ZnO particles is 100 parts by weight.
10. The negative electrode according to claim 1 , wherein the metal element is contained in the form of an oxide particle.
11. The negative electrode according to any one of claims 1 to 10, wherein the negative electrode is a sheet-like press-molded body.
12. A positive electrode and The negative electrode according to any one of claims 1 to 11, a separator that separates the positive electrode and the negative electrode in a manner capable of conducting hydroxide ions; An electrolyte; A zinc secondary battery comprising:
13. 13. The zinc secondary battery of claim 12, wherein the separator is a layered double hydroxide (LDH) separator.
14. The zinc secondary battery according to claim 13 , wherein the LDH separator is composited with a porous substrate.
15. The zinc secondary battery according to any one of claims 12 to 14, wherein the positive electrode contains nickel hydroxide and / or nickel oxyhydroxide, thereby making the zinc secondary battery a nickel-zinc secondary battery.
16. The zinc secondary battery according to any one of claims 12 to 14, wherein the positive electrode is an air electrode, thereby forming the zinc secondary battery into a zinc-air secondary battery.
Citation Information
Patent Citations
Method of manufacturing zinc electrode for alkaline storage battery
JP1978070348A
Polarization splitter
JP1986090101A
Alkaline battery, manufacture thereof, and appliance using alkaline battery
JP1995006759A
Battery
JP2001216946A
Alkaline storage battery
JP2003115323A